Effects of a brief problem-solving intervention for parents of children with cancer. Issue 1 (2nd January 2018) - Lamanna, Jennifer; Bitsko, Matthew; Stern, Marilyn
ABSTRACT: This study examines a problem-solving intervention for parents of children with cancer. It was hypothesized that the intervention would improve problem-solving ability and decrease symptoms of caregiving stress and posttraumatic stress compared controls. 39 parents were assessed at baseline, one month, and three months post-intervention. No significant results were found. This study adds to research on problem-solving interventions for parents of children with cancer. Future studies should consider timing of interventions and target parents under the highest levels of distress.